Moderate exercise with a dietary vitamin C and E combination protects against streptozotocin-induced oxidative damage to the blood and improves fetal outcomes in pregnant rats - Naziroglu, M; Simsek, M; Kutlu, M (Walter de Gruyter Gmbh, 2004)
A considerable amount of clinical and experimental evidence now exists suggesting that many biochemical pathways strictly associated with diabetes increase the production of reactive oxygen species (ROS). However, daily moderate exercise and vitamins C and E (VCE) supplementation can be beneficial to diabetes due to reducing blood glucose and free radical production. In the present study, we investigated the effect of VCE and moderate exercise on lipid peroxidation (MDA) and scavenging enzyme activity in the blood of STZ-induced diabetic pregnant rats. Fifty female Wistar rats were used and were randomly divided into five groups. The first and second were used as the control and pregnant control groups, respectively. The third group was the pregnant diabetic group. The fourth group was the diabetic-pregnant-exercise group. VCE- supplemented feed was given to pregnant-diabetic-exercise rats constituting the fifth group. Animals in the exercised groups were moderately exercised daily on a treadmill (16.1 m/min, 45 min/d) for three weeks (five days a week). Diabetes was induced on day zero of the study. Body weights in the five groups were recorded weekly. Plasma and red blood cell (RBC) samples were taken from all animals on day 20. Glutathione peroxidase (GSH-Px), catalase and reduced glutathione (GSH) levels in plasma and RBCs, glucose, vitamins A, E and beta-carotene in plasma, the number of fetuses, and body weight were lower in pregnant diabetic rats than in control animals, whereas there was a significant increase in platelet counts and plasma and RBC MDA levels. The decreased antioxidant enzymes did not improve through exercise only. However, the decreased vitamins, and increased MDA, glucose levels and white blood cell (WBC) counts were improved either by exercise or exercise plus VCE supplementation. There were no significant changes in the RBC counts and hemoglobin values in the five groups. In conclusion, these data demonstrate that there is an increase in MDA in the blood of diabetic pregnant animals, whereas there is a decrease in the number of fetuses, antioxidant vitamins and enzymes. However, dietary VCE with moderate exercise may strengthen the antioxidant defense system due to reducing ROS. They may play a role in preventing diabetes-related diseases of pregnant subjects.
Keywords: diabetes; exercise; oxidative stress; pregnancy; vitamins C and E